Análisis del control interno y su incidencia en el cumplimiento de los objetivos institucionales de la Cooperativa de Ahorro y Crédito "Nuevo Amanecer". - Cajamarca Chasi, Mayra Jissela (2017)
The investigation was carried out considering that the cooperative has a deficient Internal Control system, for that reason an analysis of the internal control and its incidence the fulfillment of the institutional objectives, to carry out the present analysis was considered the present scheme: to know the manuals of functions, procedures manual, established policies, general information. The main objective was to analyze the internal control and its incidence in the accomplishment of the institutional objectives of the cooperative of savings and credit Nuevo Amanecer, through a study mentioned. For this investigation the deductive method was applied, starting from the general data accepted as valid, to deduce by means of logical reasoning, with studies of general principles, and then to verify its validity. The inductive method starts from the facts that allows to reach a generalization and the test, which serves to obtain a global knowledge of the internal control system. The instrument used was the internal control questionnaire that was made to the manager and the accountant of the institution to know more clearly what were their shortcomings, since it is a feasible instrument to deduce the results. As a result it is specified that in the study entity, there is non-compliance by the employees, and it is made known the negative impact that gender that is not fully complied with the institutional objectives, the application of the general recommendations of the impact research technically in the internal control system to the cooperative, will socially contribute to provide adequate attention to the client, to generate trust to the clients, partners, in the financial system and optimize the resources that the institution possesses and thus contribute to the development and positioning in the financial field.